The uses of podcast easy stories in english to improve the listening skills in students from Centro Tecnológico Naval - Parrales Picazo, Luis Gabriel (2023)
This mixed method design study aimed to determine the influence of implementing the Podcast platform "Easy Stories in English" to improve the student’s listening skills in an Ecuadorian Institute. Students struggle to understand what they listen in this foreign language which is worried as this skill is a key int their military profession. As a matter of fact, using these stories in podcasts can help to become more familiar with colloquial language, accents, and pronunciation. A convenient sample of fifty A2 students participate in this research with the distribution of 25 students in the experiment class and 25 students in the control class. A quasi-experimental design with a pre-test and post-test was applied in this research. In addition, a survey questionnaire and an interview were administered to the experimental group to explore their perception of the use of this podcast in improving listening skills. Findings revealed that there is a significant difference between the two groups, favoring the experimental group. On average 90% of students have a positive attitude toward the use of these podcasts in listening in terms of motivation in learning English, listening to stories, and podcasts as excellent tools to acquire new knowledge and reinforce topics covered in classes. Students perceived that podcasts provided authentic materials, and interesting activities including listening exercises and meaningful tasks for them so they felt more motivated to learn English. This study recommended that teacher may utilize podcasts in teaching listening considering their effectiveness as a technology-based learning tool.